Anti-inflammatory and antioxidant activities of Moringa peregrina Seeds - Koheil, Mahmoud A.; Hussein, Mohammed A.; Othman, Samir M.; El-Haddad, Alaa (Free Radicals and Antioxidants)
The present study was carried out to evaluate the anti-inflammatory and antioxidant activities of Moringa peregrina seeds ethanolic and aqueous extracts. The anti-inflammatory effect Moringa peregrina extracts was examined in rats, using fresh egg albumin-induced oedema, and diclofenac (100 mg/kg) was used as reference drug for comparison. The methods selected to design a convenient system to assess the antioxidant activity of Moringa peregrina extracts including, reducing power, chelating activity on Fe2+, free radical-scavenging, total antioxidant, superoxide radical scavenging, hydrogen peroxide scavenging and hydroxyl radical scavenging activities in an attempt to understand its mechanism of action, which may pave the way for possible therapeutic applications. In addition, the results were compared with natural and synthetic antioxidants, such as α- tocopherol, ascorbic acid, butylated hydroxytoluene(BHT), butylated hydroxyanisole (BHA) and trolox. The results indicated that Moringa peregrina ethanolic and aqueous extracts (100-300 mg/kg p. o.) also dose-dependently and significantly inhibited (p < 0.05-0.001) fresh egg albumin-induced acute inflammation. Ethanolic and aqueous extracts of Moringa peregrina exhibited a strong reducing power, Fe2+ chelating effect, free radical scavenging activity, hydrogen peroxide scavenging ability, and hydroxyl radical scavenging activity. Antioxidant activity of the ethanolic and aqueous extracts increased with increased concentrations in the range of 20-140μg/ ml the extracts also exhibited a strong superoxide radical scavenging activity. This study showed that Moringa peregrina extracts exhibited antioxidant activity in all tests and the extracts could be considered as a source of natural antioxidants. Taken together, Moringa peregrina has potential as an anti-inflammatory and antioxidant agent against inflammation and free radicals and deserves clinical trial in the near future.
Keywords: Moringa peregrina; anti-inflammatory; antioxidant activity; α- tocopherol; ascorbic acid and butylated hydroxytoluene (BHT); butylated hydroxyanisole (BHA)